Clinical significance of transcription factor RUNX2 in lung adenocarcinoma and its latent transcriptional regulating mechanism. (December 2020) - Yang, Da-Ping; Huang, Wan-Ying; Chen, Gang; Chen, Shang-Wei; Yang, Jie; He, Rong-Quan; Huang, Su-Ning; Gan, Ting-Qing; Ma, Jie; Yang, Lin-Jie; Song, Jian-Hua; Mo, Jun-Xian; et al.
Graphical abstract: Highlights: RUNX2 overexpression in LUAD. LUAD patients with upregulated RUNX2 expression have poor prognoses. RUNX2 could regulate the cell cycle and MAPK signaling pathways in LUAD. Abstract: RUNX family transcription factor 2 (RUNX2) overexpression has been found in various human malignancies. However, the expression levels of RUNX2 mRNA and protein in lung adenocarcinoma (LUAD) were not investigated. This study aims to thoroughly analysis the expression level and potential mechanisms of RUNX2 mRNA in LUAD. We applied in-house immunohistochemistry, high-throughput RNA-sequencing, and gene microarrays to comprehensively investigate the expression level of RUNX2 in LUAD. A pool standard mean difference (SMD) and summary receiver operating characteristic curves (SROC) were calculated to assess the integrated expression value of RUNX2 in LUAD. The hazard ratios (HRs) were integrated to evaluate the overall prognostic effect of RUNX2 on the LUAD patients. The differentially expressed genes (DEGs) of LUAD, the potential target genes of RUNX2, and its co-expressed genes were overlapped to obtain a set of specific genes for GO and KEGG enrichment analyses. RUNX2 overexpression in LUAD was validated using a large number of cases (2 418 LUAD and 1 574 non-tumor lung samples). The pooled SMD was 0.85 (95 % CI: 0.64–1.05) and the area under the curve (AUC) of the SROC was 0.86 (95 %CI: 0.83−0.89). The integrated HR was 1.20 [1.04–1.38], indicating that increased expression of RUNX2 was an independent risk factor for the poor survival of the LUAD patients. RUNX2 and its transcriptionally regulates potential target genes may promote cell proliferation and drug resistance of LUAD by modulating the cell cycle and MAPK signaling pathways. RUNX2 can provide new research directions for targeted drug therapy and drug resistance for LUAD treatment.